Physical and Anthropometric (Somatotype) Female Badminton Athletes Aged 10-12 Years - Arianto, Oktavian; Riezky Army Riesha (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
The aim of this research was to determine the physical condition and somatotype of female badminton athletes aged 10-12 years in Semarang City. The population in this study were female athletes aged 10-12 years who had achieved achievements on the podium, totaling 10 athletes. The sampling technique is purposive sampling technique. The sample in this study consisted of 10 athletes. The instruments in this study used tests and measurements referring to physical tests aged 10-12 years (Wiyanto, 2020) and somatotype measurements using the Heath & Carter formula (Carter & Heath, 1990; Penggalih et al., 2018). The results of the physical tests for female badminton athletes aged 10-12 years were in the very good category 2 athletes (20%), in the Good category there were 6 athletes (60%) and in the Medium category there were 2 athletes (20%). The results of measuring the somatotype of female badminton athletes aged 10-12 years were in the Mesomorph category of 3 athletes (30%), in the Good category there were 7 athletes (60%) and in the Endomorph category there were none. In conclusion, female badminton athletes aged 10-12 in the city of Semarang have a good level of physical condition and are of the Ectomorph somatotype type which tends to have a tall body posture, little body fat and a small body shape.